Association between oxidative stress and vascular reactivity in children with sickle cell anaemia and sickle haemoglobin C disease. (3rd May 2017) - Möckesch, Berenike; Connes, Philippe; Charlot, Keyne; Skinner, Sarah; Hardy‐Dessources, Marie‐Dominique; Romana, Marc; Jumet, Stéphane; Petras, Marie; Divialle‐Doumdo, Lydia; Martin, Cyril; Tressières, Benoît; Tarer, Vanessa; et al.
Summary: Oxidative stress and haemolysis‐associated nitric oxide (NO) depletion plays a crucial role in the development of vasculopathy in sickle cell anaemia (SS). However it remains unknown whether oxidative stress and haemolysis levels influence vascular function in patients with sickle haemoglobin C disease (SC). Microvascular response to heat (using Laser Doppler flowmetry on finger), oxidative stress biomarkers, NO metabolites, endothelin‐1 and haematological parameters were compared between patients with SS and SC. Vascular function, oxidative and nitrosative markers were also measured in healthy (AA) children. SS and SC had increased plasma advanced oxidation protein products (AOPP), malondialdehyde, plasma antioxidant activities and NO end products, compared to AA. SC had lower catalase activity compared to AA and SS. Haemolytic rate, glutathione peroxidase and nitrotyrosine concentrations were significantly increased in children with SS compared to SC and AA. SS and SC had impaired microvascular reactivity compared to AA. In SS, the plateau phase of the response to local thermal heating was negatively associated with nitrotyrosine and AOPP. No association between vascular function parameters and oxidative stress markers was observed in SC. Mild haemolysis in SC, compared to SS, may limit oxidative and nitrosative stress and could explain the better preserved microvascular function in this group.